Molecular and Genetic Insights into Thoracic Aortic Dilation in Conotruncal Heart Defects - Kay, W. Aaron (Frontiers in Cardiovascular Medicine, 2016)
Thoracic aortic dilation (AD) has commonly been described in conotruncal defects (CTDs), such as tetralogy of Fallot, double outlet right ventricle and transposition of the great arteries, and truncus arteriosus. Several theories for this have been devised, but fairly recent data indicate that there is likely an underlying histologic abnormality, similar to that seen in Marfan and other connective tissue disease. The majority of aortic dissection in the general population occurs after the age of 45 years, and there have been very few case reports of aortic dissection in CTD. Given advances in cardiac surgery and increasing survival over the past several decades, there has been rising concern that, as patients who have survived surgical correction of these defects age, there may be increased morbidity and mortality due to aortic dissection and aortic regurgitation. This review discusses the most recent developments in research into AD in CTD, including associated genetic mutations.